An inventory model for random replenishment interval and imperfect quality items under demand fluctuation. (2016) - Panda, Shibaji; Modak, Nikunja Mohan
Continuous review and periodic review are two extensively discussed replenishment procedures for inventory problems in the literature. But, when a supplier delivers inventories to a retailer with random inter-arrival times, it is not possible to determine the retailer's order level using these two procedures. In that case, replenishment will be periodic but replenishment intervals will be random. Considering replenishment interval as independent and identically distributed random variable an inventory model is developed in which a known percentage of received items are defective. Fluctuation in demand for perfect quality inventory, arises due to the impact of several marketing parameters, is taken into account. A portion of unmet demand for perfect quality inventory is back-ordered and the rest is lost. The mathematical model is developed. Both fluctuation and no fluctuation in demand are discussed. A numerical example is presented and sensitivity analysis of the model is carried out.